Tourists and Local Residents' Perceptions of Halal Tourism Efforts in Labuan Bajo - Eugenius Adisaputra Midy; Dudi Anandya (Budapest International Research and Critics University, 2022)
Research on Local People's Perceptions of Halal Tourism Efforts in Labuan Bajo” Referring to this, practitioners and researchers recognize the importance of the tourism market (Battour and Ismail, 2016). Today the global Tourism Industry is becoming increasingly competitive. Understanding the needs, interests, demands, and behavior of international travelers is very important in destination development (Shafaei and Mohamed, 2015). The main research question of this research is